2021
DOI: 10.1002/iid3.529
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of saliva reveals association of complement system with primary Sjögren's syndrome

Abstract: Introduction: To compare the saliva proteomes of experimental Sjögren's syndrome (ESS) model mice and healthy controls to identify potential diagnostic biomarkers for primary Sjögren's syndrome (pSS).Methods: Proteins were extracted from the saliva of three ESS and three normal control mice using the data-independent acquisition technique. R language was used to identify the differentially expressed proteins (DEPs). Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were performed to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Proteomic analysis using an experimental SS mouse model revealed that salivary C3, complement factor H (CFH), serpin family G member 1 (SERPING1), fibrinogen alpha (FGA), and fibrinogen gamma (FGG) expressions were different between SS model and control mice [ 26 ]. Downregulation of salivary C3, CFH, SERPING1, FGA, FGG is associated with activation of the alternative complement system and defects in the complement system with low production of complement proteins.…”
Section: Proteomic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analysis using an experimental SS mouse model revealed that salivary C3, complement factor H (CFH), serpin family G member 1 (SERPING1), fibrinogen alpha (FGA), and fibrinogen gamma (FGG) expressions were different between SS model and control mice [ 26 ]. Downregulation of salivary C3, CFH, SERPING1, FGA, FGG is associated with activation of the alternative complement system and defects in the complement system with low production of complement proteins.…”
Section: Proteomic Analysismentioning
confidence: 99%
“…Immune complex formation and deposition are critical in the pathogenesis of autoimmune disease, including SS, and the presence of immune complexes in the serum, blood vessels, and glomeruli has been found in patients with SS. Proteomic analysis using immune complex-capturing beads and nano-LC-MS/MS identified 998 immune complex-antigen present in the saliva of nine patients with SS, but not in the saliva of seven non-SS patients [ 26 ]. Neutrophil defensin 1 and small proline-rich protein 2D were found most frequently in patients with SS.…”
Section: Proteomic Analysismentioning
confidence: 99%
“…In an experimental murine model, proteomics has recently showed a differential expression of C3 and complement factor H, together with Serpin family G member 1 (SERPING1), fibrinogen α and γ, in the saliva of SjS mice compared to controls ( Li et al, 2021 ). Patients diagnosed with SjS can present hypocomplementemia, in rates ranging between 2 and 25% for C3, 10–39.5% for C4 and 14–15% for CH50 ( Skopouli et al, 2000 ; Ioannidis et al, 2002 ; Theander et al, 2004 ; Ramos-Casals et al, 2005 ; Brito-Zerón et al, 2012 ; Brito-Zerón et al, 2018 ; Anquetil et al, 2019 ; Sebastian et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, immunological differences exist between humans and mice (8,9). Through literature review and previous research of the research group, C57BL/6 mice are found to be a typical animal model of antigen induced SS (10)(11)(12). We performed immune infiltration analyses of the pSS human salivary gland (SG) CIBERSORT (13) and pSS C57BL/6 mouse seq-ImmuCC models.…”
mentioning
confidence: 99%